Research on the Impact of Deleveraging Policy on Enterprise Green Innovation: An Empirical Study in China - Shen, Dongyang; He, Wenjian (Frontiers in Environmental Science, 2022)
By optimizing enterprises’ capital structure, the deleveraging policy has a close relationship with green innovation. Taking the Opinions on Actively and Steadily Reducing Enterprise Leverage issued by the State Council of China in 2016 as an exogenous impact and utilizing the panel date of listed manufacturing enterprises in China from 2010 to 2019, this paper constructs a DID model and conducts a series of robustness tests, which quantitatively confirms that the deleveraging policy can play a positive role in improving enterprise green innovation. Furthermore, heterogeneity analysis reveals that the deleveraging policy can promote the application of green invention patents to a greater extent, and has a greater effect on green innovation in state-owned enterprises, large-scale enterprises, technology intensive enterprises and enterprises in financially developed regions. Ultimately, the mechanism test confirms that the deleveraging policy provides long-term funds for enterprise green innovation by promoting enterprise equity financing. And with the strengthening of shareholders’ supervision and management, it also effectively ensures the stable development of green innovation.